Retracing the Tragic Hero in Sophocles’ Oedipus Rex and Philip Roth’s The Human Stain - Hassanin, Shaimaa Mohamed (Journal of Humanities & Social Sciences, 2020)
This paper reevaluates the fundamental status of Coleman Silk in Philip Roth’s The Human Stain and Oedipus in Sophocles’ Oedipus Rex by testing their characters against Aristotelian tragic hero’s elements. In spite of the verifiable comparisons to Oedipus, Coleman is not a neglected figure, but a subverted one that underpins Roth’s proposal of "the different nature" of inconceivable postmodern American tragedy. In Philip Roth’s The Human Stain, the protagonist Coleman Silk is implicitly linked to Sophocles’ classical figure Oedipus in Oedipus Rex. The plot is interwoven with allusions to Greek tragedies, but in The Human Stain Coleman lacks the stature and the real character of Oedipus. In addition, Coleman lacks, to some extent, the real elements of a tragic hero that constitute the Catharsis: the process of releasing and providing relief; a conflict which raises the question; is Coleman really a tragic hero? According to Aristotle, the tragic hero should experience a dilemma and a massive transformation from valuable standards to lower depth, and this person should suffer particularly after committing a mistake, or even thinking about his past deeds. The tragic hero should be relatively a commendable person whose comeuppance is brought about by his own fallacies which he did not commit out of defect or wickedness, but out of his own serendipity. Following the ancient Greek concept which asserts that fluke is associated with actions, Coleman is a fortuitous man at first, unlike Oedipus, despite being born as a black man. Because of this unlucky fact, he is capable of changing his identity and rising up to the level of preeminence.